PALYNOLOGICAL ASSEMBLAGES AND MACROFLORAS FROM EOCENE-MIOCENE DEPOSITS OF THE TATAR STRAIT COAST (EASTERN SIKHOTE ALIN) - Lopatina D.A. (My University, 2001)
Palynological characteristics of Eocene-Miocene deposits of the Tatar Strait coast between the Son'e and Dembi bays (eastern Sikhote Alin) are presented. The study spore-and-pollen assemblages and plant imprints show that flora-bearing deposits near the Son'e and Bui bays are comparable in age: they are of the late Eocene around the Son'e Bay and of the late Eocene-early Oligocene near the Bui Bay. Flora-bearing deposits of the Dembi Bay yield macroflora of the second half of the early Miocene and microflora of the late Oligocene-middle Miocene. When compared, the spore-and-pollen and fossil plant assemblages from corresponding units show their similarity at the generic level. Genera of anemophilous plants are common for microand macrofloral assemblages. Remains of entomophilous plants are less abundant in spore-and-pollen assemblages than among plant imprints. Judging from the composition of floral assemblages, they characterize vegetation of a moderately warm and humid climate.
Keywords: Eocene; Miocene; Sikhote Alin; Cenozoic::Neogene::Miocene; Cenozoic::Paleogene::Eocene; Кайнозой::Неоген::Миоцен; Кайнозой::Палеоген::Эоцен